The Occurrence of Hormesis in Plants and Algae - Nina Cedergreen; Jens C. Streibig; Per Kudsk; Solvejg K. Mathiassen; Stephen O. Duke (SAGE Publishing, 2007)
This paper evaluated the frequency, magnitude and dose/concentration range of hormesis in four species: The aquatic plant Lemna minor , the micro-alga Pseudokirchneriella subcapitata and the two terrestrial plants Tripleurospermum inodorum and Stellaria media exposed to nine herbicides and one fungicide and binary mixtures thereof. In total 687 dose-response curves were included in the database. The study showed that both the frequency and the magnitude of the hormetic response depended on the endpoint being measured. Dry weight at harvest showed a higher frequency and a larger hormetic response compared to relative growth rates. Evaluating hormesis for relative growth rates for all species showed that 25% to 76% of the curves for each species had treatments above 105% of the control. Fitting the data with a dose-response model including a parameter for hormesis showed that the average growth increase ranged from 9±1% to 16±16% of the control growth rate, while if measured on a dry weight basis the response increase was 38±13% and 43±23% for the two terrestrial species. Hormesis was found in >70% of the curves with the herbicides glyphosate and metsulfuron-methyl, and in >50% of the curves for acifluorfen and terbuthylazine. The concentration ranges of the hormetic part of the dose-response curves corresponded well with literature values.